2010
DOI: 10.1021/ef101107r
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Kinetic Hydrate Inhibitor Performance of a Series of Poly(N-alkyl-N-vinylacetamide)s

Abstract: Kinetic hydrate inhibitors (KHIs) have been used successfully for about the last 16 years to prevent gas hydrate formation mostly in gas and oilfield production lines. They work by delaying the nucleation and often also the growth of gas hydrate crystals for periods of time dependent mostly on the subcooling in the system. Poly(N-alkyl-N-vinylamide)s have been briefly investigated previously but no work has previously been published detailing a systematic study of structure versus performance. In this paper we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 25 publications
6
66
0
Order By: Relevance
“…Previous tests in our laboratories gave percentage variations of similar magnitude. 15 Stochasticity of hydrate formation in a small cell leads to these scatterings. In addition, there is one result in some of the test series that lies outside the distribution, which could be neglected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous tests in our laboratories gave percentage variations of similar magnitude. 15 Stochasticity of hydrate formation in a small cell leads to these scatterings. In addition, there is one result in some of the test series that lies outside the distribution, which could be neglected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was hypothesized that polyvinyl pyrrolidone (PVP), a well-known KHI, inhibits hydrate formation by adsorption through hydrogen bonds2627. Accordingly, KHI abilities of a variety of polymers18282930313233343536 on hydrate inhibition and morphological changes1737 of hydrate crystals induced by the adsorption of KHIs have been reported. However, a more recent study demonstrated that PVP has no direct contact with the hydrate surface3839, raising the possibility that adsorption is not the only mechanism of hydrate inhibition.…”
mentioning
confidence: 99%
“…One widely‐used technique uses a constant temperature stirred crystallizer, and the changes in pressure, or the amount of gas supplied to maintain a constant pressure, are recorded as the system forms hydrates . These measurements require experimental samples in the range of 20‐500 mL and experimental times in the order of 10‐15 hours per datum . Recently, we developed a novel technique that allows the use of liquid sample sizes of 20 μL and experimental times of less than an hour per datum .…”
Section: Introductionmentioning
confidence: 99%